HUBUNGAN MINAT BELAJAR DENGAN HASIL BELAJAR IPA-BIOLOGI SISWA KELAS VIII MTsN DURIAN TARUNG PADANG - Fajri, Risa Kurnia; Ardi, Ardi; Helendra, Helendra (Pendidikan Biologi, 2013)
ABSTRACT Interest and concern in the studying have a close relationship. Someone who is interested in a particular subject, usually tend to pay attention to these subjects. This research aimed to determine of relationship of interest and learning results  in the students of class VIII MTsN Tarung Padang Durian with total population 186 people. Sampling was used proportional random sampling, with a sample of 49 people. The instrument were used, a questionnaire to obtain the data of learning interest and a document learning results that obtained from teachers IPA. The data obtained were analyzed using product moment correlation of Pearson  . This study aims was to determine of a significant relationship between interest in learning  with learning result students  in class VIII MTsN Tarung Padang Durian. Results of this study show that : there is a significant positive relationship between interest in learning with learning results IPA- Biology eighth grade students MTsN.